Assessment of deep beams with inadequate web reinforcement using strut-and-tie models. (1st September 2020) - Zaborac, Jarrod; Choi, Jongkwon; Bayrak, Oguzhan
Highlights: Reinforcement crossing a crack plays significant role in STM efficiency. Max. nodal efficiency factors can be used for structures without min. reinforcement. STM can be used as a practical tool for the assessment of existing structures. Abstract: The objective of the study summarized in this paper was to evaluate the strut-and-tie design provisions of the 2017 AASHTO LRFD Bridge Design Specifications as a capacity assessment tool for structures with non-code-compliant crack control reinforcement detailing, that is, members which do not contain the minimum volume of reinforcement and/or violate the maximum allowable spacing. A database of 905 deep beam tests was filtered down to 253 tests to complete this evaluation. Six different methods for selecting concrete efficiency factors were investigated using the database. Furthermore, a case study of an approximately 60-year-old bent cap was completed. Ultimately, it was found that, with few adjustments, the current provisions could be used to estimate the capacity of structures with out-of-date reinforcement detailing practices safely and effectively.